Nanostructure of [Li(G4)] TFSI and [Li(G4)] NO3 solvate ionic liquids at HOPG and Au(111) electrode interfaces as a function of potential. Issue 1 (5th November 2014) - McLean, Ben; Li, Hua; Stefanovic, Ryan; Wood, Ross J.; Webber, Grant B.; Ueno, Kazuhide; Watanabe, Masayoshi; Warr, Gregory G.; Page, Alister; Atkin, Rob
Abstract : Atomic force microscopy (AFM) force measurements have been used to study the solvate ionic liquid (IL) double layer nanostructure at highly ordered pyrolytic graphite (HOPG) and Au(111) electrode surfaces as a function of potential. Abstract : Atomic force microscopy (AFM) force measurements have been used to study the solvate ionic liquid (IL) double layer nanostructure at highly ordered pyrolytic graphite (HOPG) and Au(111) electrode surfaces as a function of potential. Two solvate ILs are investigated, [Li(G4)] TFSI and [Li(G4)] NO3 . Normal force versus apparent separation data indicates that both solvate ILs adopt a multilayered morphology at the electrode interface, similar to conventional ILs. Calculations of adsorption free energies indicate that at 0 V the ion layer in contact with the electrode surface is enriched in the more surface active cations. When a positive or negative surface bias is applied, the concentration of counterions in the innermost layer increases, and higher push-through forces are required to displace near surface layers, indicating a stronger interfacial structure. Generally, [Li(G4)] TFSI has a better defined structure than [Li(G4)] NO3 on both electrode surfaces due to stronger cohesive interactions within layers. Interfacial structure is also better defined for both solvate ILs on HOPG than Au(111) due to the greater surface roughness of Au(111). Further, at all negative potentials on both surfaces, a small final step is observed, consistent with either compression of the complex cation adsorbed structure or desolvation of the glyme from the Li + .